Is photographic posture analysis and trunk control different in hemiparetic and diparetic children with cerebral palsy? - Betul Erbay; Pt; MSc; Nilay Comuk Balci; Pt; PhD (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2022)
Objective: Photographic posture analysis is a useful, inexpensive, time-efficient, and non-invasive method to assess posture. The primary purpose of this study was to compare PPA and trunk control between children with Diparetic and Hemiparetic Cerebral Palsy (CP).  Methods: Fifty-two children with hemiparetic and diparetic CP whose GMFCS levels I and II were compared with PPA in sitting position and also trunk control was measured with Trunk Control Measurement Scale (TCMS).  Results: There was no scientific difference in craniovertebral angle, sagittal head tilt, sagittal shoulder-C7 angle, thoracic kyphosis angle, coronal head tilt, coronal shoulder angle, coronal pelvic angle in PPA and TCMS between groups (p>0.05), however, there was a scientific difference in lumbar lordosis angle in PPA between the groups (p<0.05).  Conclusion: Lumbar lordosis is more common in children with hemiparetic CP than diparetic CP. It can be thought that this situation requires children to change their body biomechanics to compensate their affected sides more than the children with diparetic CP. The physicians should take care of the postural alignment of the lumbar and pelvic girdle of hemiparetic CP. We think that muscle strength, muscle shortness, and other lower extremity biomechanics that could increase lordosis should be examined in detail in hemiparetic CP regardless of where the origin of lumbar lordosis (pelvis or lumbar region).